Evaluating the Association Between Tectonic Tremors and Earthquakes in Taiwan From 7 Years Catalogs. Issue 4 (17th April 2019) - Peng, Wei; Chen, Kate Huihsuan; Toda, Shinji
Abstract: Knowledge of what governs the interaction between slow‐ and fast‐slip earthquakes is essential to understanding the nature of the earthquake cycle. In southern Taiwan, four major earthquakes (2008 M w 5.2 Taoyuan, 2010 M w 6.4 Jiashian, 2012 M w 5.9 Wutai, and 2016 M w 6.4 Meinong events) that occurred near the active tremor areas provide a unique opportunity to analyze their spatiotemporal association. With the declustered tremor catalog built in this study, we were able to statistically evaluate the possible association between tremor and mainshock‐aftershock sequences in space and time. We found that close‐by mainshocks influences tremor's timing in a matter of less than 5 days by short‐term triggering, while the 2010 M L 6.4 Jiashian earthquake appears to be most responsible for such triggering. Assuming a low dip angle thrust faulting mechanism, tremors coincided with small static stress increases (8 kPa) in the 2010 M L 6.4 Jiashian earthquake. The other three major events, however, caused either negative or neglectable stress changes in the tremor zone. The different responses of the tremors can be explained by coseismic slip‐induced static stress change. In this complex tectonic region as a boundary between continental subduction and collision, the interaction between slow‐ and fast‐slip phenomena could be facilitated by a commonly high fluid pressure environment. Key Points: We explore the spatiotemporal association between tremors and earthquakes using 7‐year tremor and earthquake catalog In a confined distance of 5 km, a greater percentage of earthquakes tend to occur in 5 days prior to the tremors A commonly high fluid pressure environment may be needed, to facilitate their interaction